Why we need to fix the global energy governance architecture - Cheema, Abdur Rehman; Haris, M. (2024)
The current global energy governance architecture is not likely to deliver what the world badly needs to address the climate crisis. Unless drastic changes are introduced, COP30 in Brazil next year is going to be another failure to deliver actionable outcomes.